A study of trilateral flash cycles for low-grade waste heat recovery-to-power generation - Ajimotokan, Habeeb A. (Cranfield University, 2014)
There has been renewed significance for innovative energy conversion technologies, particularly the heat recovery-to-power technologies for sustainable power generation from renewable energies and waste heat. This is due to the increasing concern over high demand for electricity, energy shortage, global warming and thermal pollution. Among the innovative heat recovery-to- power technologies, the proposed trilateral flash cycle (TFC) is a promising option, which presents a great potential for development. Unlike the Rankine cycles, the TFC starts the working fluid expansion from the saturated liquid condition rather than the saturated, superheated or supercritical vapour phase, bypassing the isothermal boiling phase. The challenges associated with the need to establish system design basis and facilitate system configuration design-supporting analysis from proof-of-concept towards a market-ready TFC technology are significant. Thus, there is a great need for research to improve the understanding of its operation, behaviour and performance. The objective of this study is to develop and establish simulation tools of the TFCs for improving the understanding of their operation, physics of performance metrics and to evaluate novel system configurations for low-grade heat recovery-to-power generation. This study examined modelling and process simulation of the TFC engines in order to evaluate their performance metrics, predictions for guiding system design and parameters estimations. A detailed thermodynamic analysis, performance optimization and parametric analysis of the cycles were conducted, and their optimized performance metrics compared. These were aimed at evaluating the effects of the key parameters on system performances and to improve the understanding of the performance behaviour. Four distinct system configurations of the TFC, comprising the simple TFC, TFC with IHE, reheat TFC and TFC with feed fluid-heating (or regenerative TFC) were examined. Steady-state steady-flow models of the TFC power plants, corresponding to their thermodynamic processes were thermodynamically modelled and implemented using engineering equation solver (ESS). These models were used to determine the optimum synthesis/ design parameters of the cycles and to evaluate their performance metrics, at the subcritical operating conditions and design criteria. Thus, they can be valuable tools in the preliminary prototype system design of the power plants. The results depict that the thermal efficiencies of the simple TFC, TFC with IHE, reheat TFC and regenerative TFC employing n-pentane are 11.85 - 21.97%, 12.32 - 23.91%, 11.86 - 22.07% and 12.01 - 22.9% respectively over the cycle high temperature limit of 393 - 473 K. These suggest that the integration of an IHE, fluid-feed heating and reheating in optimized design of the TFC engine enhanced the heat exchange efficiencies and system performances. The effects of varying the expander inlet pressure at the cycle high temperature and expander isentropic efficiency on performance metrics of the cycles were significant. They have assisted in selecting the optimum-operating limits for the maximum performance metrics. The thermal efficiencies of all the cycles increased as the inlet pressures increased from 2 - 3 MPa and increased as the expander isentropic efficiencies increased from 50 - 100%, while their exergy efficiencies increased. This is due to increased net work outputs that suggest optimal value of pressure ratios between the expander inlets and their outlets. A comprehensive evaluation depicted that the TFC with IHE attained the best performance metrics among the cycles. This is followed by the regenerative TFC whereas the simple TFC and reheat TFC have the lowest at the same subcritical operating conditions. The results presented show that the performance metrics of the cycles depend on the system configuration, and the operating conditions of the cycles, heat source and heat sink. The results also illustrate how system configuration design and sizing might be altered for improved performance and experimental measurements for preliminary prototype development.
Keywords: Waste heat recovery-to-power; power cycle; trilateral flash cycle; process integration; modelling; process simulation; energy analysis; exergy analysis; performance optimization; parametric analysis; performance comparison